Adsorption Isotherm of Cr(VI) Using Mg/Al Hydrotalcite with Molar Ratio 2:1 - Bayu Wiyantoko; Puji Kurniawati; Tri Esti Purbaningtias (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2014)
Hydrotalcite is a material which is used in various application and one of them as an adsorbent of Cr(VI). Hydrotalcite was synthesized using co-precipitation method with Al(NO3)3.9H2O and Mg(NO3)2.6H2O as raw materials. This research aim to study the initial concentration and adsorption isotherm of Cr(VI) by using Mg/Al hydrotalcite in 180 minutes contact time. The Optimum initial concentration of Cr(VI) was 675 mg/L with 55,57 mg/g adsorption capacity. Isotherm adsorption was studied using Langmuir and Freundlich model. Based on the result, the adsorption of Cr(VI) fitted well with Langmuir isotherm model by 0,997 coefficient of determination